2020
DOI: 10.1186/s12963-020-00214-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical inactivity as a risk factor for all-cause mortality in Brazil (1990–2017)

Abstract: Background The aim of this study was to estimate the mortality from all causes as a result of physical inactivity in Brazil and in Brazilian states over 28 years (1990–2017). Methods Data from the Global Burden of Disease (GBD) study for Brazil and states were used. The metrics used were the summary exposure value (SEV), the number of deaths, age-standardized mortality rates, and the fraction of population risk attributable to physical inactivity. Results The Brazilian population presented risk of exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
0
16
1
1
Order By: Relevance
“…A pre-analysis of the burden attributable to the group of RF of the GDB was conducted with estimates from the 2015 GBD 3 and later, in 2016, with revised estimates 6 , showing that a unhealthy diet, metabolic RFs, alcohol, and tobacco consumption are important protagonists in the overall death and disease burden in Brazil. More recent studies evaluated the burden attributable to specific RFs, such as hypertension 7 , obesity 8 , hyperglycemia 9 , physical inactivity 10 , and smoking 11 . However, those estimates were not calculated together, which hindered the comparison between the RFs and their consequences in the overall disease burden.…”
Section: Introductionmentioning
confidence: 99%
“…A pre-analysis of the burden attributable to the group of RF of the GDB was conducted with estimates from the 2015 GBD 3 and later, in 2016, with revised estimates 6 , showing that a unhealthy diet, metabolic RFs, alcohol, and tobacco consumption are important protagonists in the overall death and disease burden in Brazil. More recent studies evaluated the burden attributable to specific RFs, such as hypertension 7 , obesity 8 , hyperglycemia 9 , physical inactivity 10 , and smoking 11 . However, those estimates were not calculated together, which hindered the comparison between the RFs and their consequences in the overall disease burden.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the risk of the Brazilian population in relation to low levels of physical activity has been stable over the years (SEV) (but the ideal scenario is further improvements in the levels of physical activity for the population). The stability observed in SEV can be due to public policies implemented in Brazil especially after 2006 to improve the levels of physical activity in the population 11,[18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…An analytical study based on estimates of the global burden of diseases for Brazil made by GBD 2019 was carried out, coordinated by the Institute for Health Metrics and Evaluation (IHME) in partnership with the Ministry of Health of Brazil 2 , 9 - 11 . In the mortality analysis, information from the Mortality Information System of the Ministry of Health was used, with adjustment for the underreporting of deaths and declaration of undefined/nonspecific causes, called garbage codes 2 , 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Physical inactivity is a global health problem that increases the risk of cardiovascular disease, type 2 diabetes, obesity, and pISSN 1975-8375 eISSN 2233-4521 cancer, and impairs health-related quality of life [1][2][3][4]. Worldwide, more than a quarter of the population does not get enough physical activity (PA), with a 4.2% increase in the number of people between 2010 and 2016 [5]; furthermore, physical inactivity is more prevalent among females and in countries with high income inequality [6].…”
Section: Introductionmentioning
confidence: 99%